Educational process mining: literature classification, gaps, and emerging opportunities - Semler, Rosaine F.; Semler, Jhonnatan R.; Wehrmeister, Marco A.; Southier, Luiz F. P.; Casanova, Dalcimar; Teixeira, Marcelo (Frontiers in Education, 2025)
Process Mining (PM) is a well-known approach for workflow analysis and has the Educational PM (EPM) as its education-oriented version. Despite promising applications, the EPM literature landscape is quite unclear in reporting the bridge between the existing tools, techniques, research groups, main frontiers, and, especially, main directions to guide future efforts. These gaps induce initiatives to be conducted empirically and disconnected from each other, preventing efforts from converging. This paper presents a Systematic Literature Review (SLR) that collects a reliable set of results on EPM and classifies their predominant profile and contributions. A total of 4,312 articles were identified, of which only 35 remained after removing duplicates and applying exclusion criteria. After peer review, 5 more articles were removed, and the references of the 30 articles were subjected to snowballing. This resulted in 28 more candidate articles, from which 14 remained after applying the exclusion criteria, and were joined with the other 30, totaling 44 articles. After closer and individual inspection, 28 articles remained to compose the final portfolio. They were then analyzed, and insights were provided based on their combined contributions, which allowed us to evidence the main gaps in EPM and how they could be fulfilled in future research. These findings can be used as a starting point for initiatives that aim to demarcate new frontiers of EPM.